Surgical removal of large mucocele in a young patient: case report - Milena Sierra Drumond da COSTA; Carla Cristina dos Santos MARTINS; Marília Gabriela Corrêa MOMESSO; Ana Paula Rocha Carvalho Bernardes de ANDRADE; Renata Cristiane da Silva MOLINA; Paola Fernanda Leal CORAZZA (Faculdade São Leopoldo Mandic, 2019)
Mucocele is a term applied to the clinical manifestation of phenomena that may affect the minor salivary glands. There are different forms of treatment reported in the literature, including total enucleation. The objective of this study is to describe a surgical technique for removal of Mucocele in a teenage patient. A 16-years-old, female, attended the sector of Pediatric Dentistry of Camilo Castelo Branco University - campus São Paulo / SP. The patient's main complaint was "a bubble in the mouth that punchs and fills again, feeling salty taste." At the clinical examination, a circumscribed, mucosa-like, floating-palpation lesion was observed, with a 1.7 cm diameter in the lower lip, with characteristics similar to Mucocele. In the planning of the case, we opted for the surgical removal treatment with anatomopathological analysis. The prognosis for the surgical removal of the lesion was very favorable due to some established criteria: age of the patient, location, depth and size of the lesion.